Associação do polimorfismo G894T do gene da óxido nítrico sintase endotelial (eNOS) com alteração do intervalo QTc e marcadores de risco cardiovascular em pacientes dialíticos - Andrade, Jessica Liara Felicio de [UNIFESP] (2016)
Introduction: The chronic kidney disease (CKD) occurs due to traditional (hypertension, diabetes, dyslipidemia) and non-traditional risk factors (inflammatory processes and oxidative stress). In addition, the CKD can collaborate with major cardiac changes such as QTc prolongation, contributing to the cardiovascular disease (CVD) risk and premature death. The endothelial nitric oxide synthase (eNOS) - which can be inhibited by asymmetric dimethylarginine (ADMA) - is an enzyme of great importance for cardiovascular system homeostasis, and one of the responsible for nitric oxide (NO) production, which is a potent vasodilator. There are three eNOS polymorphisms, among them, the G894T polymorphism resulting from the replacement of nitrogenous base guanine for thymine at position 894 of exon 7, and it is correlated with cardiac complications and mortality in this population. Aim: To evaluate the association of G894T polymorphism with QTc prolongation and cardiovascular risk markers in dialysis patients. Methods: Predialysis blood samples were collected for biochemical and genetic analysis and was the 12-lead electrocardiogram performed. The genotype distribution of eNOS G894T polymorphism was analyzed by polymerase chain reaction (PCR), followed by digestion with Ban II restriction enzyme. Cardiovascular risk factors were assessed by NO, TBARS, ADMA and total antioxidant plasma levels. Results: The study showed that GG genotype was predominant, with 54%, followed by 41% GT and 6% TT and this genotype distribution was not associated with QTc prolongation; however, women with TT genotype presented a trend tendency to this change and patients with T allele had increased levels of lipid peroxidation, L-arginine and ADMA and reduced synthesis of NO and antioxidant. Conclusion: Our study showed that, although there was no association between eNOS polymorphisms and QTc, patients with T allele had significant risk factors for the development among them, increased oxidative stress, decreased NO bioavailability and redox imbalance, which contribute to the development of endothelial dysfunction and therefore for future cardiovascular complications.